SLC45A4 is a pain gene encoding a neuronal polyamine transporter - Middleton, Steven J.; Markússon, Sigurbjörn; Åkerlund, Mikael; Deme, Justin C.; Tseng, Mandy; Li, Wenqianglong; Zuberi, Sana R.; Kuteyi, Gabriel; Sarkies, Peter; Baskozos, Georgios; Perez-Sanchez, Jimena; Farah, Adham; et al. (Nature, 2025)
Polyamines are regulatory metabolites with key roles in transcription, translation, cell signalling and autophagy1. They are implicated in multiple neurological disorders, including stroke, epilepsy and neurodegeneration, and can regulate neuronal excitability through interactions with ion channels2. Polyamines have been linked to pain, showing altered levels in human persistent pain states and modulation of pain behaviour in animal models3. However, the systems governing polyamine transport within the nervous system remain unclear. Here, undertaking a genome-wide association study (GWAS) of chronic pain intensity in the UK Biobank (UKB), we found a significant association between pain intensity and variants mapping to the SLC45A4 gene locus. In the mouse nervous system, Slc45a4 expression is enriched in all sensory neuron subtypes within the dorsal root ganglion, including nociceptors. Cell-based assays show that SLC45A4 is a selective plasma membrane polyamine transporter, and the cryo-electron microscopy (cryo-EM) structure reveals a regulatory domain and basis for polyamine recognition. Mice lacking SLC45A4 show normal mechanosensitivity but reduced sensitivity to noxious heat- and algogen-induced tonic pain that is associated with reduced excitability of C-polymodal nociceptors. Our findings therefore establish a role for neuronal polyamine transport in pain perception and identify a target for therapeutic intervention in pain treatment.